The CGIAR Initiative on Aquatic Foods: Gender Equality and Social Inclusion Strategy - Adam, Rahma; Kruijssen, Froukje; Amani, Anamika; Pyburn, Rhiannon; Farnworth, Cathy; Mudege, Netsayi; Mapedza, Everisto; Choudhury, Afrina; Haque, S. M. Faridul; Shenoy, Neetha; Eam, Dyna; Sok, Sao; et al. (WorldFish, 2023)
This CGIAR Initiative on Aquatic Foods: Gender Equality and Social Inclusion (GESI) Strategy provides guidance on how to undertake AqFS research for development through a gender lens. The strategy’s main objectives are: (i) to ensure that there is gender inclusiveness and responsiveness in technological, social, financial and institutional innovations; (ii) to provide avenues for wealth generation and improving livelihoods of people relying on small-scale fisheries (SSFs) and sustainable aquaculture; (iii) to pave the way for inclusive governance of land and water commons; and (iv) to provide guidance on how to tackle underlying social norms and structural barriers through gender-transformative approaches (GTAs).